2019
DOI: 10.1073/pnas.1906833116
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal deletion of Na V 1.1 channels in mice causes thermal seizures and cognitive deficit characteristic of Dravet Syndrome

Abstract: Dravet Syndrome is a severe childhood epileptic disorder caused by haploinsufficiency of the SCN1A gene encoding brain voltage-gated sodium channel NaV1.1. Symptoms include treatment-refractory epilepsy, cognitive impairment, autistic-like behavior, and premature death. The specific loci of NaV1.1 function in the brain that underlie these global deficits remain unknown. Here we specifically deleted Scn1a in the hippocampus using the Cre-Lox method in weanling mice. Local gene deletion caused selective reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 42 publications
7
51
0
1
Order By: Relevance
“…An increase in core temperature causes generalized seizures in Scn1a ‐/+ mice 12 and in mice with local hippocampal Na V 1.1 ablation, 9 reflecting the early febrile seizures often observed in infants with Dravet syndrome 1,2 . We therefore tested whether seizures could also be induced by hyperthermia in our Scn1a ‐/+ (n = 7) and AAV‐GFP‐Cre‐injected Scn1a fl/fl (hippocampus: n = 4; cortex: n = 5) mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in core temperature causes generalized seizures in Scn1a ‐/+ mice 12 and in mice with local hippocampal Na V 1.1 ablation, 9 reflecting the early febrile seizures often observed in infants with Dravet syndrome 1,2 . We therefore tested whether seizures could also be induced by hyperthermia in our Scn1a ‐/+ (n = 7) and AAV‐GFP‐Cre‐injected Scn1a fl/fl (hippocampus: n = 4; cortex: n = 5) mice.…”
Section: Resultsmentioning
confidence: 99%
“…The hippocampus has been suggested as a primary driver of epileptiform activity in a mouse model of Dravet syndrome 8 . In addition, Stein et al 9 recently demonstrated that local ablation of Na V 1.1 channels restricted to hippocampus results in an increased sensitivity to thermally evoked seizures. Because patients with SCN1A mutations may manifest with focal (cortical) epilepsy, 10,11 the relevance of various brain regions is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…There are conflicting results regarding the neuronal basis of Dravet, with evidence for reduced inhibition De Stasi et al, 2016;Ogiwara et al, 2007;Rubinstein et al, 2015b;Tai et al, 2014;Yu et al, 2006) that might be transient (Favero et al, 2018), as well as indications of increased activity of excitatory neurons (Liu et al, 2013;Mistry et al, 2014). Here, we focused on the hippocampal CA1 region, which has been shown to be important for Dravet epilepsy (Stein et al, 2019), examining the function of CA1 pyramidal neurons and stratum oriens interneurons (O-LM) at the three stages of Dravet. Within the CA1 microcircuit, recurrent collaterals of CA1 pyramidal cells activate O-LM interneurons, which in turn mediate feedback inhibition of these same excitatroy neurons (Klausberger and Somogyi, 2008;Müller and Remy, 2014;Scanziani and Pouille, 2004) (Fig.…”
Section: Reduced Intrinsic Excitability Of O-lm Cells At the Onset Ofmentioning
confidence: 95%
“…Here, we focused on the hippocampal CA1 region, which has been shown to be important for Dravet epilepsy (Stein et al, 2019), examining the function of CA1 pyramidal neurons and stratum oriens interneurons (O-LM) at the three stages of Dravet. Within the CA1 microcircuit, recurrent collaterals of CA1 pyramidal cells activate O-LM interneurons, which in turn mediate feedback inhibition of these same excitatroy neurons (Klausberger and Somogyi, 2008;Müller and Remy, 2014;Scanziani and Pouille, 2004) (Fig.…”
Section: Reduced Intrinsic Excitability Of O-lm Cells At the Onset Ofmentioning
confidence: 99%
“…Nevertheless, studies of adult DS mice, featuring selective deletion of Scn1a in parvalbumin-and somatostatinexpressing inhibitory neurons, reported mild epilepsy with cognitive deficit (Rubinstein et al, 2015a;Tatsukawa et al, 2018). Similarly, local deletions of Scn1a in the hippocampus caused either mild or no epilepsy, with cognitive deficits (Bender et al, 2016(Bender et al, , 2013Stein et al, 2019). These results suggest that cognitive deficits, similarly to motor impairment and hyperactivity may also be independent of the epilepsy.…”
Section: Behavioral Alterations In Ds Mice During the Febrile Stagementioning
confidence: 94%